2015
DOI: 10.14737/journal.aavs/2015/3.4.233.244
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Antibacterial Activities of Cranberry Extract against E. coli O157:H7 in Urinary Tract Infected Rats

Abstract: | The objective of this study was to determine the in-vitro and in-vivo activity of cranberry extracts against Escherichia coli O157:H7. This strain of E. coli was the most common etiologic agent of urinary tract infections isolated from patients. Filter sterilized aqueous and methanol extract of cranberry was prepared and used in the present study. The aqueous extract of cranberry produced inhibition zone ranging from (10.8 -23.8) mm against the tested bacteria. While the methanol extract produces larger zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The result of bacterial count was agreement with [51]. Also, that was agreement with [34,35]they demonstrated that within 7 days of Egypt. J. Vet.…”
Section: Urine Bacterial Countsupporting
confidence: 88%
See 1 more Smart Citation
“…The result of bacterial count was agreement with [51]. Also, that was agreement with [34,35]they demonstrated that within 7 days of Egypt. J. Vet.…”
Section: Urine Bacterial Countsupporting
confidence: 88%
“…55, No. 6 (2024) causing urinary tract infection in female rats by injecting pathogenic E. coli O157:H7 through inoculating the rats with (2.6 10 6 ) CFU/ml led to effective colonization of E. coli O157H:7 [ 34]. Plantaricin could inhibit the growth of E.coli [29].…”
Section: Urine Bacterial Countmentioning
confidence: 99%
“…To the best of our knowledge, there are no in vivo studies relevant to the antibacterial activity of anthocyanins from blueberries. However, Ibrahim et al [ 93 ] showed that cranberry anthocyanin extracts (200 mg/kg b.w aqueous and methanol extracts) were effective in treating UTI caused by E. coli O157:H7 in infected rats. Although the anthocyanin profiles are not exactly the same in blueberries and cranberries, we might expect a similar behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Enterobacteriaceae and Staphylococci has already negatively affected β-lactam-based therapy, so it is assumed that in near future a complete resistance to most effective β-lactam agents is going to surface [18][19][20]. In our study, we have tried to explore the effect of a natural derivative, cranberry fruit extract as it has adjuvant properties of interfering the resistance and can also enhance the efficacy of β-lactam agents.…”
Section: Discussionmentioning
confidence: 99%
“…The content of flask was filtered through what man and evaporated to dryness in oven at 50°C. After the cranberry fruit powder had been obtained, different concentrations of cranberry fruit extract (20,30,40, 50 and 60 mg/ml) were prepared by mixing the cranberry fruit powder with dimethyl sulfoxide (DMSO) and stored at 4°C in air tight bottles [14].…”
Section: Preparation Of Cranberry Fruit Extract (Cfe)mentioning
confidence: 99%